Manipulation of micro particles and nodes formation through standing surface acoustic waves - Gai, Cherng Sean (Nanyang Technological University, 2020)
The ability to manipulate micro particles creates a lot of potential applications such as in biology, 3D printing as well as in micro fluidics. There are various types of techniques that can manipulate micro particles. One of the technique is the utilization of surface acoustic waves to handle micro particles and as it is still a relatively new technique to manipulate micro particles as compared to other techniques, researches are still being conducted to fully understand the manipulation of micro particles by utilizing surface acoustic waves. During the project, a commercial software will be used to conduct simulations. The software used is COMSOL Multiphysics and it will be utilized to visualize the distribution of acoustic pressure across a micro chamber subjected to standing surface acoustic waves. Following that, an experiment will be conducted to observe the formations of pressure nodes along with the pressure anti-nodes including how does adjusting the phase difference of surface acoustic waves affects where the pressure nodes and anti-nodes are located so as to manipulate the micro particles. The results obtained from the experiment will then be compared to the results of the simulation so that the results from the simulation can validate the results from the experiment. Results obtained from the experiment and simulation showed that having a presence of standing surface acoustic waves will produce pressure nodes along with pressure anti-nodes and after measurement, it has been found that the measurement from the pressure node to its neighbouring pressure anti-node is half of the input wavelength. Furthermore, it has also been validated that adjustments made to the difference in phase of the surface acoustic wave leads to changes of the placement of the pressure nodes as well as pressure anti-nodes and this enables the manipulation of micro particles.